THE CONSEQUENCES OF DEFAMATION IN HAMKA’S NOVEL TERUSIR - Wahyuningsih, Mukti; Manugeren, M.; Pardi, Pardi (JOURNAL OF LANGUAGE, 2024)
Defamation is an act that harms an individual’s reputation through the spread of false statements. It is commonly categorized into two forms: libel, which involves written defamation, and slander, which refers to spoken or direct defamation. This research focuses on slander as a form of defamation that deeply impacts Mariah, the protagonist in Hamka’s novel Terusir. The study examines the consequences of defamation on Mariah, who, as a victim, endures severe hardships and social alienation. Adopting a sociological approach to literature, this research situates defamation within the context of real-world social dynamics, emphasizing its destructive potential within both fictional and actual communities. Using a descriptive qualitative method, data were gathered from the novel’s narrative, as well as from monologues and dialogues. Terusir by Hamka serves as the primary data source, supplemented by secondary references that enhance the contextual analysis. Findings reveal that Mariah suffers extensively from defamation: she is publicly shamed and expelled from her home by her husband during a stormy night, symbolizing her isolation and loss of dignity. This defamatory act not only tarnishes Mariah’s identity as a respected mother and wife but also severs her relationship with her son, leading her into a state of near madness fueled by profound emotional turmoil and an overwhelming sense of loss.